Association of cystatin C kidney function measures with motoric cognitive risk syndrome: evidence from two cohort studies - Lijun Xu; Weihao Xu; Lijie Qin (The Journal of Nutrition, Health and Aging)
Background: This study aimed to examine the associations of cystatin C, cystatin C estimated glomerular filtration rate (eGFRcys), and the difference between eGFRs (eGFRdiff) using cystatin C and creatinine levels with incident motoric cognitive risk syndrome (MCR). Methods: We utilized data from two nationally representative cohort studies, the China Health and Retirement Longitudinal Study (CHARLS, 2011–2015) and the US Health and Retirement Study (HRS, 2010–2018). Baseline serum cystatin C and creatinine levels were measured, and eGFRcys and creatinine estimated GFR (eGFRcr) were calculated. MCR was defined as subjective cognitive complaints plus objectively measured slow gait speed. Multivariable logistic models were used to investigate the longitudinal associations between kidney function measurements and incident MCR. Results: In CHARLS (N = 2,085) and HRS (N = 1,240) cohorts, 7.4% and 7.2% developed MCR over follow-up. Each SD increment in serum cystatin C level was associated with elevated incident MCR odds, and an inverse association of eGFRcys with incident MCR was observed in both cohorts after multivariable adjustment and meta-analyses.The association between serum cystatin C and incident MCR remained significant even after adjusting for serum creatinine, suggesting that cystatin C is independently associated with MCR, regardless of kidney function levels. Additionally, each SD decrease in the absolute value of eGFRdiff was associated with lower odds of incident MCR among CHARLS participants. Conclusions: Cystatin C and eGFRcys were correlated with an elevated MCR risk in two distinct populations. Specifically, eGFRdiff also related to incident MCR among Chinese older adults. Monitoring cystatin C-based kidney function could have significant clinical utility for identifying incident MCR risk, and represents a potential intervention target for healthier cognitive aging.